Out of a Writing Conference: Speaking Writing Connection - Utami Widiati (TEFLIN Journal: A publication on the teaching and learning of English, 1997)
Abstract: In our TEFL situation, it is simply in the classroom that we expect our students to get the language exposures as much as possible since the language is not used outside the classroom. Therefore, every opportunity in the teaching learning process should be geared towards the students using the target language.This paper highlights how oral communication skills can be encouraged even in a writing class. With a paradigmatic change in the teaching of writing, teachers do not value only `the product but also `the process. When translated into the classroom, one of the features of this new paradigm, the writing process approach, is `the conference, which occurs between teacher and students as well as between students. As Mol (1992) states, writing conference provides students with immediate, meaningful responses to their writing, developing students ability to reflect upon their own writing and the writing of others in a critical and constructive way. Looking back at our own experience in teaching writing, the conference does not only scaffold the students in the process of meaning-making but also creates an atmosphere where they are actively engaged in a `more focused talk. This is of paramount importance since our students tend to speak in their native language even in the classroom.